Local pH induced electrochemical CO2 reduction on nanostructured Ag for adjustable syngas composition. (1st November 2021) - Lim, Jungae; Lim, Hyungseob; Kim, Bupmo; Kim, Soo Min; Lee, Jong-Bae; Cho, Kang Rae; Choi, Hansaem; Sultan, Siraj; Choi, Wonyong; Kim, Wooyul; Kwon, Youngkook
Highlights: Nanostructured Ag electrocatalyst was fabricated via simple electrochemical chlorination-dechlorination process. Elongated chlorination process yields thicker nanostructure and larger CO selectivity. Complex nanostructure traps key intermediates near the surface, inducing change in the local pH. Higher pH promotes the CO2 reduction at the expense of the HER. CO/H2 composition could be tuned by varying the chlorination time and thus the extent of a change in local pH near the surface of the fabricated Ag electrocatalyst. Abstract: Carbon monoxide is an industrially significant chemical because it is an essential precursor for the Fisher-Tropsch process. However, solid fuels such as coal yield syngas with H2 :CO ratio of ∼0.7, which is unideal for hydrocarbon chain growth. Herein, we present electrochemical CO2 reduction to adjustable H2 /CO syngas ratio by controlling the thickness of silver nanostructure. By looking into the local species generated during the electrolysis using the in-situ ATR-FTIR, the increased amount of anions such as OH − and CO3 2− trapped within the porous structure, which increases with the thickness of the nanostructure, leads to an increase in local pH near the electrode surface, and thus at the expense of the HER, the CO production is promoted. As a result, syngas composition can be adjusted simply by controlling the thickness of the nanostructure. Graphical abstract: Nano-structured silver electrocatalyst capable of producing syngas at desirable H2 /CO ratio by controlling thickness of the nanostructure and the local pH Image, graphical abstract